Bubble column fluid dynamics: A novel perspective for flow regimes and comprehensive experimental investigations. (February 2021) - Besagni, Giorgio
Highlights: A comprehensive theory to describe flow regimes in bubble columns is proposed Comprehensive experimental investigations are conducted Global and local flow properties are experimentally obtained Five gas spargers are tested The influence of the aspect ratio and liquid phases are discussed Abstract: When a gas phase is injected into a liquid phase, it gives rise to a rich, fascinating and mysterious fluid dynamic phenomenology. The lack of knowledge regarding this phenomenology, a shortcoming in the design and operation of multi-phase reactors, is related to the absence of an unique definition of the flow regimes. To date, different studies gave different definitions of the flow patterns and, subsequently they experimentally obtained some global and local flow properties, with no physical-based description of the flow patterns. Is there a theory able to determine a-priori the boundaries of different flow regimes (and, thus, the flow regime for a given set of boundary conditions, given the phases and the system design)? Answering this question requires changing the present point of view in defining and describing the flow regimes and it is the primary motivation of this paper. To achieve this goal, a new theory has been formulated, which changes the present way of approaching bubble columns and which is based on the following statement: the fluid dynamics in gas-liquid bubble columns is interpreted by means of a general relationship―built upon five flow regime transitions―between two global fluid dynamic parameters. The strategic path to formulate this theory is, first, to go back to the pioneering studies and formulate basic relationships on the basis of a general principle. Subsequently, in order to support and verify the theory a comprehensive and multi-scale experimental investigation has been performed and coupled with previous experimental studies. The different experimental studies have been conducted in a gas-liquid large-scale bubble column (height of 5.3 m; inner diameter of 0.24 m) operated in the batch and in counter-current modes; to study all flow regimes, the bubble column was tested with five gas spargers (viz., pipe sparger in open tube and annular gap configuration, spider sparger, two different perforated plates and needle spargers) with different values of the aspect ratios and different liquid phases. It was found that, in an air-water bubble column, the gas velocity is approximately 0.03 m/s either in the case of the destabilization of the mono-dispersed homogeneous flow regimes or in the case of the destabilization of the pseudo-homogeneous flow regimes. Increasing the gas sparger opening induces a narrowing of the boundaries between the transitional flow regimes; conversely, increasing the bubble column aspect ratio destabilizes the existing flow regimes up to some critical values. Also, increasing the superficial liquid velocity in the counter-current mode destabilizes the homogeneous flow regime. Finally, it has been observed that the prevailing effect of the liquid phase, in a bubble column operated with a " coarse " gas sparger, is to change the boundary of the homogenous flow regime. It has also been discussed how the change in coordinates of the flow regime transition between the homogeneous and the heterogeneous flow regimes is caused by the changes in the size distribution. This study is intended to outline a precise definition of the flow regimes in bubble columns and it poses a rational basis for future studies.